ҚАДРИЯТЛАРНИ ҚАДРЛАШ-ГУМАНИСТИК ВАЗИФАМИЗДИР - Таспанова, Ж. (FAN va JAMIYAT, 2018)
The article presents the ideas and thoughts values, about the cause-and consecutive-events and devotion, to material and spiritual values.